Establishment of Five Canine Lymphoma Cell Lines and Tumor Formation in a Xenotransplantation Model - YAMAZAKI, Jumpei; OKUDA, Masaru; KUBO, Masahito; HAYASHI, Toshiharu; TSUJIMOTO, Hajime; SUZUKI, Ryoichi; EMA, Yasuo; OKAMURA, Yasuhiko; TANI, Kenji; HIRAOKA, Hiroko; UMEKI, Saori; MIZUNO, Takuya (Journal of Veterinary Medical Science, 2013)
Five novel, canine lymphoma cell lines (Ema, CLC, CLK, Nody-1 and UL-1) were established from dogs suffering from lymphoma and characterized in vitro and in vivo. All cell lines, except CLC, were characterized with T-cell phenotypes, by flow cytometric analysis and polymerase chain reaction for antigen receptor rearrangement. Cell proliferation rates and transcriptional levels of MYC, PTEN, KIT and FLT3 varied between each cell line. Intraperitoneal xenotransplantation of Ema, CLC, Nody-1 and UL-1 lymphoma cell lines into NOD/SCID mice induced ascites, intraperitoneal tumors and severe infiltration of lymphoma cells into the pancreas and mesentery. Establishment of novel canine lymphoma cell lines with different characteristics is critical for elucidating the pathophysiology of canine lymphoma and improving current therapies.